2012
DOI: 10.2528/pierl12042009
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Wavelength Demultiplexer for DWDM Application Using 1-D Photonic Crystal

Abstract: Abstract-Transmission characteristics of 1-D photonic crystal (PC) structure with a defect have been studied. We consider a Si/ZnS multilayer system. We also consider the refractive index of both layers to be dependent on temperature and wavelength simultaneously. The refractive indices of Si and ZnS layers are functions of temperature as well as of the wavelength of incident light. This property can be used to tune the defect modes at desired wavelength. As defect modes are function of temperature, one can tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…In an RoF system, the cost-effective and high quality generation of high frequency mm-wave signals is a key technology that requires further development toward high-frequency bands, especially for frequencies above 40 GHz [12][13][14]. Compared with the conventional electrical method, the optical method is preferable [15][16][17]. By beating the two high-order optical sidebands with good coherence in a square-law photodetector (PD), a laser with an optical external phase or intensity modulator is a promising and attractive technology for the generation of high-frequency mm-wave signals, the frequency of which can be several-folds that of the radio frequency (RF) local oscillator [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In an RoF system, the cost-effective and high quality generation of high frequency mm-wave signals is a key technology that requires further development toward high-frequency bands, especially for frequencies above 40 GHz [12][13][14]. Compared with the conventional electrical method, the optical method is preferable [15][16][17]. By beating the two high-order optical sidebands with good coherence in a square-law photodetector (PD), a laser with an optical external phase or intensity modulator is a promising and attractive technology for the generation of high-frequency mm-wave signals, the frequency of which can be several-folds that of the radio frequency (RF) local oscillator [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…It is also observed that the line width of the defect mode is not affected by the variation of the incident angle. Hence the proposed structure may be used as a single channel tunable wavelength division demultiplexer for DWDM systems [11,17,18]. Also, the line-width of the transmitted wavelength is 0.42 nm, so the proposed structure is an attractive candidate to be used to demultiplexing the signal with 0.8 nm separation, which corresponds to the ITU grid for DWDM.…”
Section: Resultsmentioning
confidence: 99%
“…In a RoF system, the cost-effective and high quality generation of high frequency MMW signals with simple implementation and low cost is a key technique that needs further development, especially for the frequency beyond 40 GHz [9][10][11][12]. The optical method is preferable over the conventional electrical method [13,14]. Various techniques have been developed, such as the stimulated Brillouin scattering (SBS) in optical fiber [15], the use of four-wave mixing in a highly nonlinear fiber (HNLF) [16], and the optical frequency up-conversion using an external modulator, such as LiNbO 3 MZM [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%